On loving thyself: Exploring the association between self-compassion, self-reported suicidal behaviors, and implicit suicidality among college students. Issue 4 (8th June 2021) - Zeifman, Richard J.; Ip, Jennifer; Antony, Martin M.; Kuo, Janice R.
Abstract: Objective: Suicide is a major public health concern. It is unknown whether self-compassion is associated with suicide risk above and beyond suicide risk factors such as self-criticism, hopelessness, and depression severity. Participants: Participants were 130 ethnically diverse undergraduate college students. Methods: Participants completed self-report measures of self-compassion, self-criticism, hopelessness, depression severity, and suicidal behaviors, as well as an implicit measure of suicidality. Results: Self-compassion was significantly associated with self-reported suicidal behaviors, even when controlling for self-criticism, hopelessness, and depression severity. Self-compassion was not significantly associated with implicit suicidality. Conclusions: The findings suggest that self-compassion is uniquely associated with self-reported suicidal behaviors, but not implicit suicidality, and that self-compassion is a potentially important target in suicide risk interventions. Limitations and future research directions are discussed.